Pengaruh Green Product, Perceived Value, Kredibilitas Influencer, dan Brand Image terhadap Keputusan Pembelian Skincare NPURE pada Generasi Z - Umaiya, Umaiya (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of Green Product, Perceived Value, Influencer Credibility, and Brand Image on the Purchase Decision of NPURE skincare products among Generation Z. The research employed a quantitative method with a descriptive and causal approach. The population consisted of green skincare users in the Jakarta area, with a sample of 180 Generation Z respondents who had used NPURE skincare products. The sampling technique used was purposive sampling, and data were collected through an online questionnaire. Data analysis used multiple linear regression with SPSS. The results showed that partially, Green Product (t count 3.320; sig. 0.001), Perceived Value (t count 2.662; sig. 0.009), and Influencer Credibility (t count 2.459; sig. 0.015) had a positive and significant effect on Purchase Decision. Meanwhile, Brand Image (t count 1.807; sig. 0.072) did not have a significant partial effect. Simultaneously, all four variables had a significant effect on Purchase Decision with an Adjusted R Square value of 0.496, meaning that 49.6% of the variation in Purchase Decision could be explained by the four variables, while the remaining 50.4% was influenced by other factors outside the research model. These findings indicate that Generation Z considers environmental friendliness, perceived value, and influencer credibility more than brand image in their purchase decisions for NPURE skincare products.